Species of Russula subgenera Archaeae, Compactae and Brevipedum (Russulaceae, Basidiomycota) from Dinghushan Biosphere Reserve - Xie, Xiu-Chao; Buyck, Bart; Song, Yu (European Journal of Taxonomy, 2023)
Three novel species collected from Dinghushan Biosphere Reserve (DHSBR) in southern China, Russula cylindrica Y.Song sp. nov. and R. lacteocarpa Y.Song sp. nov. in subgenus Archaeae and R. reticulofolia Y.Song sp. nov. in subg. Compactae, are described based on morphological and molecular data. In addition, Russula leucobrunnea Y.Song nom. nov. is proposed in replacement of R. leucocarpa nom. illeg. in subg. Brevipedum, as R. leucocarpa (T.Lebel) T.Lebel had been described earlier. Differences between the three novel species and their closely related taxa were analyzed. Another two known species in subg. Brevipedum, R. callainomarginis J.F.Liang & J.Song and R. japonica Hongo were also identified among specimens from DHSBR and are described and illustrated. Phylogenetic analyses of ITS and a five-locus phylogeny (concatenated LSU, mtSSU, rpb1, rpb2 and tef1) support the recognition of these taxa.